PROCESS CAPABILITY STUDY FOR IMPROVEMENT OF PRODUCT RELIABILITY AT FOOD AND BEVERAGE INDUSTRY - Rasib A.H.A.; Musazzali M.; Abdullah R.; Boejang H.; Hanizam H.; Rafaai Z.F.M. (Taylor's University, 2024)
Despite the numerous challenges faced by competitors in the same sectors, particularly in the Food and Beverage (F&B) industries, manufacturing has improved its performance. Process capability refers to a process ability to produce a product or service that meets the customer's specifications. The issue is that the manufactured items are delivered to customers that not meeting their expectations. The purpose of this study is to develop an understanding of a product reliability through process capability study factors that occur during the industrial production and how they can be applied by converting the manual activities to automated activities. Through assumption, this study influenced the outcome of the Cp and Cpk which calculated by Minitab software as a method for measuring the quality performance through identifying the production's process wide tolerances. In this study, the Cp's results are 0.86, when the Cp's results is less than 1.0, then the process is incapable. Therefore, it is necessary to think for action to be taken. Based on the Cp's results, it is helpful for level of managers, and any companies to use Cp's results as a guideline in order to increase their product's reliability through appropriate improvement while reducing process tolerances. Finally, water volume can be monitored and take an action for improvement based on Cp's results. School of Engineering, Taylor's University.